The Effectiveness of The Technique of Secreting Breast Milk on Breast Milk Production in Post-Partum Women - Ardiana Batubara; Tri Marini Supriharti Ningsih; Fitriyani Pulungan (Health Notions, 2017)
The technique of secreting breast milk can be influenced by two factors: production and secretion. Breast milk production is influenced by prolactin hormone while secretion is influenced by oxytocin hormone. The suggested technique is by using hands and fingers because they are practical, effective, and efficient, compared with using pumps. If this technique is done effectively and accurately, there will be no problem in producing breast milk and the technique of secreting it so that babies can always obtain breast milk. The objective of the research was to find out the effectiveness in the technique of secreting breast milk on breast milk production in post-partum women. The research used pre-experimental method with One-Shot Case Study (X O) design. The population was 30 primipara post-partum women who had normal childbirth in Klinik Dermawati, Klinik Tanjung, and Klinik Nurhalma, Medan, and all of them were used as the samples (total population). The data were analyzed by using ANOVA test. The result of the research showed that there was the difference in the technique of secreting breast milk on its production at p-value=0.002. The technique of secreting it by doing oxytocin massage was more effective on its production than using marmet technique and warm compress, viewed from the mean value of oxytocin massage which was higher (171.00) and standard deviation of 5.676 than using marmet technique at the mean value of 166.00 and standard deviation of 4.595 and using warm compress at the mean value of 160.50 and standard deviation of 7.246. The group which was significantly different was the technique of oxytocin massage and warm compress (p=0.002) which indicated that there was the difference in action which was done on breasts. It is recommended that the Health Agency of Medan collaborate with the Indonesian Midwife Association to make oxytocin permanent procedure as post-partum service and provide counseling for pregnant and breastfeeding women. Keywords: Technique of secreting breast milk, Breast milk production